FORMATION OF MEDIA SCIENCE INFRASTRUCTURE BIG DATA SCIENCE IN THE AGE OF HIGH ELECTRONICS - Yu. D. Gensitskiy (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is aimed to analyze the specificity of formation of media infrastructure of science under the influence of digital media distribution technology, the changing nature of scientific activity, implementation of communication researchers using Big Data. Methodology. The implementation of the purpose is seen in the use of scientific and theoretical basis of the philosophy of science, mediaphilosophy, mediaphilosophical approach to understanding society, science and technology, use of publications on selected topics of research. Originality. It was considered the problem of scientific communication change under the influence of Big Data. Forming of media infrastructure of science under the influence of media technology was analyzed. Conclusions. The emergence, formation and development of mediainfrastructure makes the world scientific community see the modernist paradigm of scientific knowledge production, pay attention to the formation of a qualitatively new ways of transmission and reception using scientific evidence and information research. At the same time there is a need for simultaneous and comprehensive study of the potential negative effects of media technologies for researchers and educational activities. Note the complications self-identification individual simulation processes and phenomena that occurs reliance on empirical base. Also there is a problem controllable and selection of information: the huge flow of information of different kinds of content depth and complicate the selection and broadcast meaningful knowledge.